Divorce by Consent in Roman Law and Contemporary Law - Ignjatović, Marija V; Kitanović, Tanja B (Zbornik radova Pravnog fakulteta u Novom Sadu, 2013)
The subject matter of this paper is divorce by mutual consent in Roman law and contemporary law. In the first part of this article, the authors analyzes the key tenets of consensual divorce in Roman law, with specific reference to the impact of Christian religious teaching on the concepts of marriage and divorce as well as on the Roman rulers’ constitutions, which marked the beginning of the process of restricting the right to divorce. In the central part of the paper, the authors examines the regulation on the consensual divorce in some contemporary legal systems. In addition, the authors provides a substantial analysis of the normative framework on the termination of marriage in the positive Serbian legislation. In the final part of the paper, the authors provides a comparative analysis and underscores the observed similarities and differenced in the regulation of the institute of consensual divorce in Roman law and in the contemporary legislation.
Keywords: contemporary law; Serbian law; Emperor Constantine; Christianity; Roman law; consequences of divorce; spouses; divorce by consent